(untitled) (UNIHumanitas, 2022)
Part of the learning process of students in the context of constructivism is oriented to build and encourage creativity in them with study techniques that best suit their learning needs. The study describes the influence of study techniques on the academic performance of students in the third cycle of Basic School Education in a public school in the city of Encarnación. The students organize their study time and homework, know and apply study techniques. The most used are underlining, summarizing, and concept maps. However, it is difficult for them to recognize the main idea, they always use the same techniques, they work in pairs; a minority does not use the techniques despite the fact that teachers encourage their use in class. Study techniques favor peer learning; they serve as feedback and fixation of learning, are very useful for closing units, as well as for the fixation and evaluation of learning; they favor student metacognition and self-reflection of teaching practice.